dUTPase-minus caprine arthritis-encephalitis virus is attenuated for pathogenesis and accumulates G-to-A substitutions. - Turelli, P (1997)
The importance of the virally encoded dUTPase for CAEV replication, invasiveness, pathogenesis, and genetic stability was investigated in goats infected by viruses with single point (DU-G) and deletion (DU-1) mutations of the dUTPase gene (DU gene). The DU gene was found to be dispensable for CAEV replication in vivo as judged by times taken to seroconvert, frequencies of viral isolation, and tissue distribution of viral RNAs. DU- reversion at week 34 in one of three goats infected with the single point mutant DU-G, however, suggested that the viral dUTPase confers some advantages for replication in vivo. Moreover, we show that dUTPase is necessary for the timely development of bilateral arthritic lesions of the carpus. Finally, dUTPase was shown to efficiently prevent accumulation of G-to-A transitions in the viral genome.